IT and the east : - Popkin, James M. (Harvard Business School Press, 2007)
The center of gravity in the technology world has shifted east. Today, India and China are churning out some of the world's best-trained computer science and electrical engineering graduates. In both countries, consumer classes and domestic markets for technology have ballooned. Western high-tech firms are increasingly sourcing their products' assembly from India and China and the innovation that drives those products. Meanwhile, indigenous Indian and Chinese companies are creating intellectual property and innovations that will compete with those same Western companies. In "IT and the East", James M. Popkin and Partha Iyengar examine the vital questions these developments raise: What's the long-term impact of high-tech outsourcing? How will innovation be managed in the future? Can Western firms compete in Asian markets while protecting key intellectual property? Will the innovation engine inexorably shift east? What would such a shift mean for Western countries currently driving innovation? The authors also discuss the emerging alliances between Indian and Chinese technology companies and outline the implications for Western businesses. Filled with extensive interviews with high-level executives, government officials, and academics from around the world, "IT and the East" is the first book to articulate the challenges that new business scenarios and capabilities in India and China pose for Western technology firms.